Components of the flavonoid nature of plants of the family Lamiaceae Lindl., having fungicidal activity against the phytopathogens of tomatoes and soybean (Experimental biology, 2017)
The results of biochemical analysis of water-ethanol extracts of some plant species of the family Lamiaceae Lindl for the presence of substances of flavonoid nature are presented in the article. It was found that extracts of Monarda citriodora and Ocimum basilicum contain components close to routine and quercetin; in extract of Hyssopus officinalis - components close to flavone and quercetin; in the extract of Satureja hortensis components are close to flavone and routine. It is shown that the sum of flavonoid compounds Monarda citriodora, sweet-scented basil and hyssop medicinal have a fungicidal effect on all the isolated pathogens of tomato and soybean fungus diseases, with the greatest effect on A. alternata (the diameter of the pathogen inhibition zone was 40 mm, 35 mm and 30, respectively). It was found that rutin slightly suppressed the growth of F.oxysporum (diameter of the suppression zone 5 mm); flavone inhibited the growth of A. alternata, F.oxysporum and P. infestans (the diameters of the absence zones were 10, 6 and 10 mm, respectively); Quercetin, as well as flavone also suppressed the growth of A. alternata, F.oxysporum and P. infestans (the diameters of the zones of absence of growth were 6, 15 and 5 mm, respectively).
Keywords: Lamiaceae Lindl., extract, components, flavonoids, fungicidal effect.